The Influence of Cultural Livelihood and Humogo Waterfall Sites (Naming Language Toponymy Point of View) - Harefa, Afore Tahir; Lase, Libertina; Gulo, Linda Mariani (English Teaching and Linguistics Journal (ETLiJ), 2024)
This research aims to describe the influence of the livelihood of the Idanoi village community on the naming of Humogo Waterfall and the descriptive toponymy language used in naming the 3 levels of Humogo Waterfall. This research uses a qualitative descriptive method. The data source in this research is the influence of community livelihoods with the naming of Humogo waterfall and descriptive toponymy language in naming 3 levels of Humogo waterfall by using interview techniques with informants to obtain data. This research was conducted in three stages, namely the data collection stage, the data analysis stage, and the stage of presenting the results of data analysis. Data collection was carried out using observation techniques, and interviews. Data analysis was carried out by analyzing what livelihoods have an influence on the naming of Humogo waterfall and how descriptive the toponymy language is used at the 3 levels of waterfalls. Based on the data analysis results, two livelihoods influence the naming of Humogo Waterfall, namely animal husbandry and agriculture/plantations. In contrast, the 3 levels of waterfalls use descriptive toponymy whose naming eyes are by the surrounding nature. This naming involves the local language used so that it can be one way to preserve the local language.